“Provider discretionary power practices to support implementation of patient-centered HIV care in Lusaka, Zambia” - Mwamba, Chanda; Mukamba, Njekwa; Sharma, Anjali; Lumbo, Kasapo; Foloko, Marksman; Nyirenda, Herbert; Simbeza, Sandra; Sikombe, Kombatende; Holmes, Charles B.; Sikazwe, Izukanji; Moore, Carolyn Bolton; Mody, Aaloke; et al. (Frontiers in Health Services, 2022)
Introduction Traditional patient-provider relationships privilege the providers, as they possess the formal authority and clinical knowledge applied to address illness, but providers also have discretion over how they exercise their power to influence patients' services, benefits, and sanctions. In this study, we assessed providers' exercise of discretionary power in implementing patient-centered care (PCC) practices in Lusaka, Zambia. Methods HIV clinical encounters between patients on antiretroviral therapy (ART) and providers across 24 public health facilities in Lusaka Province were audio recorded and transcribed verbatim. Using qualitative content analysis, we identified practices of discretionary power (DP) employed in the implementation of PCC and instances of withholding DP. A codebook of DP practices was inductively and iteratively developed. We compared outcomes across provider cadres and within sites over time. Results We captured 194 patient-provider interactions at 24 study sites involving 11 Medical Officers, 58 Clinical Officers and 10 Nurses between August 2019 to May 2021. Median interaction length was 7.5 min. In a hierarchy where providers dominate patients and interactions are rapid, some providers invited patients to ask questions and responded at length with information that could increase patient understanding and agency. Others used inclusive language, welcomed patients, conducted introductions, and apologized for delayed services, narrowing the hierarchical distance between patient and provider, and facilitating recognition of the patient as a partner in care. Although less common, providers shared their decision-making powers, allowing patients to choose appointment dates and influence regimens. They also facilitated resource access, including access to services and providers outside of scheduled appointment times. Application of DP was not universal and missed opportunities were identified. Conclusion Supporting providers to recognize their power and intentionally share it is both inherent to the practice of PCC (e.g., making a patient a partner), and a way to implement improved patient support. More research is needed to understand the application of DP practices in improving the patient-centeredness of care in non-ART settings.